Antimicrobial Activity Of Leaf Extract Of Ocimum Gratissimum L.As An Antiseptic And As Antifungal Agent - HOSAMANI.P.A; LAKSHMAN.H.C; SANDEEPKUMAR.K; SHYAMKUMAR.V (International Journal of Pharma and Bio Sciences, 2012)
Antimicrobial activity of leaf extract of Ocimum gratissimum L was studied using different solvent like chloroform, acetone, ethanol and water against bacterial strains like Bacillus subtilis, Staphylococcus aureus, Escherichia coli ,Pseudomonus aeruginosa and fungal strains Aspergillus niger and Penicillum chrysogenum. The antimicrobial activity was determined by disc diffusion method. Out of the four extract used, chloroform and acetone extracts were found to be highly active against Staphylococcus aureus and Pseudomonas aeruginosa